Beginning Eleventy a practical introduction to the Eleventy static site generator - Libby, Alex (Apress, 2022)
Leverage the power of Eleventy to quickly produce static sites that are efficient and fast. This project-oriented book simplifies the process of setting up Eleventy and manipulating content, using little more than a text editor or free software. It will equip you with a starting tool set that you can use to develop future projects or incorporate into your existing workflow. More importantly, you'll take websites to the next level, reducing the reliance on tools that are bloated, prone to being hacked and not the most efficient. Beginning Eleventy is an excellent resource for getting acquainted with creating and manipulating blogs using a static site generator approach. It takes the view that you don't have to create something complex and unwieldy; you can build something quickly, then extend it using the power of the API and plugins over time, without sacrificing speed or features. What You'll Learn: Implement the Eleventy framework in a project Explore some of the options for customizing content using the framework Gain an appreciation of pointers around maintenance requirements, and how this might compare to other blog systems Work through some example projects, to help build up a working blog from standalone demos to implementing with other tools or libraries This Book Is For? Website developers who are already familiar with JavaScript, who are looking for a fast and simple framework to deliver high quality results fast Developers who are looking to leverage the Eleventy framework to quickly create an online blog using little more than a text editor, producing optimized content in modern browsers using tools they will already have Those in agile development teams, where time is of the essence and need to deliver high quality results quickly.